Inhibition of GABARAP or GABARAPL1 prevents aminoglycoside- induced hearing loss - Jinan Li; Seung-Il Oh; Chang Liu; Bo Zhao (Proceedings of the National Academy of Sciences, 2025)
Aminoglycosides (AGs) are highly potent, broad-spectrum antibiotics frequently used as first-line treatments for multiple life-threatening infections. Despite their severe ototoxicity, causing irreversible hearing loss in millions of people annually, no preventive therapy has been approved. We previously reported that GABARAP and several other central autophagy proteins are essential for AG-induced hearing loss. This finding opens avenues for the rational design and development of inhibitors that selectively target proteins in this pathway, thereby mitigating AG ototoxicity. In this study, we generated a mouse model with a targeted deletion of GABARAPL1, a homolog of GABARAP, and another model deficient in both GABARAP and GABARAPL1. We found that normal hearing is unaffected by the depletion of these proteins. Remarkably, both proteins are essential for AG-induced hearing loss, with GABARAP playing a more significant role. To further explore the therapeutic potential, we designed and validated short hairpin RNAs targeting the mouse and human GABARAP gene. By inhibiting GABARAP expression in inner ear hair cells using adeno-associated virus-mediated RNA interference, we successfully prevented AG-induced hair cell death and subsequent hearing loss. Our findings underscore the critical role of GABARAP in AG ototoxicity and highlight its potential as a therapeutic target for preventing AG-induced hearing loss.